Factors associated with regular non-diet soft drink intake among adults in Pelotas, Southern Brazil - Rombaldi, Airton José; Neutzling, Marilda Borges; Silva, Marcelo Cozzensa da; Azevedo, Mario Renato; Hallal, Pedro Curi (Revista de Saúde Pública, 2011)
OBJECTIVE: To assess factors associated with regular intake of non-diet soft drinks among adults. METHODS: Population-based cross-sectional study including 972 adults (aged 20 to 69) in the city of Pelotas, Southern Brazil, conducted in 2006. The frequency of non-diet soft drink intake in the 12 months prior to the study was evaluated by the question: "In general since last